Sensory Devices for Older Adults with Behavioural Disturbances in the Emergency Department: A Descriptive Study - Cabilan, C.J.; Meyer, Audrey; Elmore, Rebecca; Nash, Terry; Eley, Robert; Tuckett, Anthony (Slack Incorporated, 2021)
Nonpharmacological strategies are advocated for the management of behavioral disturbance in older adults due to risk of harm from pharmacological therapy; however, limited evidence supports their use in emergency departments (EDs). The current descriptive study was conducted to investigate the use of sensory devices for nonpharmacological management of behavioral disturbance and their perceived impact. Data were collected from the sensory device registry, electronic medical records, and survey. Patient-level data (N = 33) showed that sensory devices, such as tactile blankets or toys and music, can be used in EDs to alleviate behavioral disturbance among older adults. ED staff (n = 22) expressed an interest to increase device supply. A patient and caregiver (n = 2) suggested that the devices be initiated earlier in ED care. Further research is required to strengthen evidence on the impact of these devices on patient outcomes.